Homes of the future: unpacking public perceptions to power the domestic hydrogen transition - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Elsevier, 2022)
Decarbonization in several countries is now linked to the prospect of implementing a national hydrogen economy. In countries with extensive natural gas infrastructure, hydrogen may provide a real opportunity to decarbonize space heating. While this approach may prove technically and economically feasible in the long-term, it is unclear whether consumers will be willing to adopt hydrogen-fueled appliances for heating and cooking should techno-economic feasibility be achieved. In response, this paper develops an analytical framework for examining hydrogen acceptance which links together socio-technical barriers and social acceptance factors. Applying this framework, the study synthesizes the existing knowledge on public perceptions of hydrogen and identifies critical knowledge gaps which should be addressed to support domestic hydrogen acceptance. The paper demonstrates that a future research agenda should account for the interactions between acceptance factors at the attitudinal, socio-political, market, community, and behavioral level. The analysis concludes that hydrogen is yet to permeate the public consciousness due to a lack of knowledge and awareness, owing to an absence of information dissemination. In response, consumer engagement in energy markets and stronger public trust in key stakeholders will help support social acceptance as the hydrogen transition unfolds. Affordability may prove the most critical barrier to the large-scale adoption of hydrogen homes, while the disruptive impacts of the switchover and distributional injustice represent key concerns. As a starting point, the promise of economic, environmental, and community benefits must be communicated and fulfilled to endorse the value of hydrogen homes.
Keywords: Hydrogen homes; Hydrogen economy; Domestic hydrogen; Social acceptance; Socio-technical barriers; Decarbonization